Thermodynamic investigations of Cd-Zn-Ga liquid solutions - Behera C.K.; Shamsuddin M. (My University, 2025)
Activity of zinc in liquid Cd-Zn-Ga alloys has been measured by electrochemical technique based on molten salt electrolyte galvanic cell in the temperature range 723 to 823 K along three pseudo-binary lines of Zn-(Cd y Ga1-y ), where y = 0.75, 0.50, and 0.25. The excess molar free energy, enthalpy, and entropy were computed by the Darken's treatment of the ternary solutions using published data of the relevant binary solutions and the ternary system investigated. The excess molar free energy surface of the ternary confirms substantially what one would expect from the knowledge of the corresponding curves of the component binary systems. The excess molar free energy surfaces have the maxima in the Cd-Ga side. The extremum value of molar excess free energy was found to be 3.24 kJ/mol (x Cd = 0.5, x Zn = 0.125, and x Ga = 0.375) at 800 K. The excess molar enthalpy curves have been found to be tilted toward the Zn-Cd and Cd-Ga sides. The extremum value of excess molar enthalpy was found to be 2.58 kJ/mol (x Ga = 0.3 and x Zn= x Cd = 0.35) at 800 K. The excess molar entropy surfaces have the maxima in the Zn-Ga side and minima in the Cd-Ga side. The slope-intercept method was used to compute the partial molar quantities. The activities are computed from the partial molar excess free energy for three components at 800 K. The isoactivity surfaces of the three components are depicted by the isoactivity lines. The activities of all three components show positive deviation from the Raoult's law. The excess molar free energies of the Cd-Zn-Ga system obtained experimentally are compared with those estimated from the theoretical models. © 2008 The Minerals, Metals & Materials Society and ASM International.